2007
DOI: 10.1074/jbc.m700575200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase V Allows Bypass of Toxic Guanine Oxidation Products in Vivo

Abstract: Reactive oxygen and nitrogen radicals produced during metabolic processes, such as respiration and inflammation, combine with DNA to form many lesions primarily at guanine sites. Understanding the roles of the polymerases responsible for the processing of these products to mutations could illuminate molecular mechanisms that correlate oxidative stress with cancer. Using M13 viral genomes engineered to contain single DNA lesions and Escherichia coli strains with specific polymerase (pol) knockouts, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 70 publications
5
87
0
Order By: Relevance
“…The mixtures were transformed into SOS-induced, electrocompetent wild-type AB1157 E. coli cells and the isogenic E. coli cells that are deficient in Pol II, Pol IV, Pol V or all three polymerases, following the previously published procedures (23). In this vein, the SOS system was induced by irradiating the E. coli cells with 254 nm light at a dose of 45 J/m 2 , as described previously (24). We chose to conduct the replication experiments in SOS-induced cells because of the relatively low bypass efficiencies for most of the O 2 -alkyldT lesions ( vide infra ), and we found that the bypass efficiency for O 2 -EtdT in wild-type AB1157 cells was elevated by ∼3-fold upon SOS induction.…”
Section: Methodsmentioning
confidence: 99%
“…The mixtures were transformed into SOS-induced, electrocompetent wild-type AB1157 E. coli cells and the isogenic E. coli cells that are deficient in Pol II, Pol IV, Pol V or all three polymerases, following the previously published procedures (23). In this vein, the SOS system was induced by irradiating the E. coli cells with 254 nm light at a dose of 45 J/m 2 , as described previously (24). We chose to conduct the replication experiments in SOS-induced cells because of the relatively low bypass efficiencies for most of the O 2 -alkyldT lesions ( vide infra ), and we found that the bypass efficiency for O 2 -EtdT in wild-type AB1157 cells was elevated by ∼3-fold upon SOS induction.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the glycosylases, cells lacking one of three other repair proteins (AlkB, PhrB, SmbC [see below]) display greatly increased sensitivity. When the number of DNA replication-blocking lesions exceeds the capacity of the repair proteins involved in the direct removal of lesions, a third level of protection from killing ensues: translesion synthesis mediated by Pol V (56, 64) occurs, as shown here by the increased sensitivity to kanamycin of umuC mutants deficient in Pol V. Note that Pol V has been shown to allow bypass of toxic guanine oxidation products (50). (The role of dinB-encoded Pol IV translesion synthesis [29,66] here is less clear [ Fig.…”
Section: Figmentioning
confidence: 95%
“…This includes (but is not limited to) N 2 -acetylaminofluorene (AAF) and N 2 -aminofluorene (AF) modified guanines (80, 162, 177, 226), benzo[ a ]pyrene diol epoxide (BaP) guanine and adenine adducts (129, 162, 208), 8-oxoguanine (8-oxoG) and other guanine oxidation products (141, 163, 164), oxidized abasic lesions (118), N 2 -dG and other acrolein-induced and related adducts (102, 103, 157, 265), butadiene-induced guanine intrastrand and N 2 -N 2 -guanine interstrand crosslinks (41, 121), and alkylated bases (52). By using the single-lesion containing vectors in in vitro reconstituted reactions and by introducing them into strains lacking one or more TLS polymerase, it is straightforward to determine the contribution of each polymerase to the efficiency and accuracy of in vivo lesion bypass.…”
Section: Phenotypes Of E Coli Strains With Deletions Of Pol II Iv Omentioning
confidence: 99%